Impact of Platelet Transfusion Thresholds on Outcomes of Patients With Sepsis: Analysis of the MIMIC-IV Database. Issue 4 (28th April 2022) - Zhou, Wei; Fan, Chenyu; He, Shuangjun; Chen, Yi; Xie, Cuiying
ABSTRACT: Background: The benefits of platelet thresholds for transfusion remain unclear. This study assessed the effect of two transfusion thresholds on the survival outcomes of patients with sepsis and thrombocytopenia. Methods: In this retrospective cohort study, data of patients with sepsis admitted to an intensive care unit (ICU) and who had received platelet transfusion were extracted from the Medical Information Mart for Intensive Care IV database. Patients were classified into the lower-threshold group (below 20, 000/μL) and higher-threshold group (20, 000–50, 000/μL), based on thresholds calculated from their pretransfusion platelet count. The endpoints included 28- and 90-day mortality, red blood cell (RBC) transfusion, ICU-free days, and hospital-free days. Results: There were 76 and 217 patients in the lower-threshold and higher-threshold groups, respectively. The higher-threshold group had a higher rate of surgical ICU admission (35.0% vs. 9.2%) and lower quick Sequential Organ Failure Assessment (qSOFA) score than the lower-threshold group. In the higher-threshold group, 94 (43.3%) and 132 (60.8%) patients died within 28 and 90 days, compared to 51 (67.1%) and 63 (82.9%) patients in the lower-threshold group (adjusted odds ratio, 1.96; 95% confidence interval, 1.16 to 3.03; P  = 0.012; adjusted odds ratio, 2.04; 95% confidence interval, 1.16 to 3.57; P  = 0.012, respectively). After stratification by mortality risk, the subgroup analysis showed a consistent trend favoring higher-threshold transfusion but reached statistical significance only in the low-risk group. There were no differences in red blood cell transfusion, ICU-free days, and hospital-free days between the groups. The E -value analysis suggested robustness to unmeasured confounding. Conclusions: In patients with sepsis and thrombocytopenia, platelet transfusion at a higher threshold was associated with a greater reduction in the 28- and 90-day mortalities than that at a lower threshold.